A new ophiacanthid brittle star (Echinodermata, Ophiuroidea) from sublittoral crinoid and seagrass communities of late Maastrichtian age in the southeast Netherlands - Thuy,Ben; Numberger-Thuy,Lea; Jagt,John W.M. (PeerJ, 2020)
A new species of brittle star, Ophiomitrella floorae, is recorded from the lower two meters of the Gronsveld Member (Maastricht Formation), of late Maastrichtian age (c. 66.7 Ma). These relatively fine-grained biocalcarenites reflect shallow-water deposition in a sheltered setting with a relatively firm sea floor and clear waters, under middle sublittoral and subtropical conditions. Associated echinoderm taxa comprise more robust, sturdy-plated ophiomusaid and ophiodermatid brittle stars and numerous bourgueticrinine sea lilies. The new brittle star described herein belongs to a family whose present-day members are predominantly restricted to bathyal depths. Its small size and the exceptional preservation of a single articulated specimen partially wrapped around the stalk of a bourgueticrinine suggest that O. floorae n. sp. was probably epizoic and specifically associated with stalked crinoids.
Keywords: Ophiacanthidae; Maastricht formation; Deep-water taxa; Epizoic lifestyle; Cretaceous